1995
DOI: 10.1002/ana.410380115
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of familial and sporadic hyperekplexia

Abstract: Hyperekplexia is a rare, autosomal dominant neurological disorder characterized by hypertonia, especially in infancy, and by an exaggerated startle response. This disorder is caused by mutations in the alpha 1 subunit of the inhibitory glycine receptor (GLRA1). We previously reported two GLRA1 point mutations detected in 4 unrelated hyperekplexia families; both mutations were at nucleotide 1192 and resulted in the replacement of Arg271 by a glutamine (R271Q) in one case and a leucine (R271L) in the other. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 30 publications
2
84
0
4
Order By: Relevance
“…g, relative efficacy (I max /EC 50 ) of A275T/wild-type GlyT2. basis than dominant hyperekplexia, which received initial attention because of the characterization of extended families (8,9) harboring dominant GLRA1 mutations such as R271 Q/L. In common with previous studies (17,18), genotype-phenotype analysis revealed that GlyT2 mutations in humans are not as severe as those observed in mice, dogs, and cattle, where mutations in SLC6A5 cause extreme muscle rigidity, tremor, difficulty in breathing, and early mortality (19,20,44).…”
Section: Discussionmentioning
confidence: 78%
“…g, relative efficacy (I max /EC 50 ) of A275T/wild-type GlyT2. basis than dominant hyperekplexia, which received initial attention because of the characterization of extended families (8,9) harboring dominant GLRA1 mutations such as R271 Q/L. In common with previous studies (17,18), genotype-phenotype analysis revealed that GlyT2 mutations in humans are not as severe as those observed in mice, dogs, and cattle, where mutations in SLC6A5 cause extreme muscle rigidity, tremor, difficulty in breathing, and early mortality (19,20,44).…”
Section: Discussionmentioning
confidence: 78%
“…Glycine receptors also have a role in processing visual and auditory signals (69). There are a number of known malfunctions of CLRs including mutations of muscle nAChRs, which lead to congenital myasthenic syndromes, mutations of GABAA and nAChRs cause epilepsy (70), and glycine receptor mutations lead to hyperekplexia (71,72).…”
Section: Cys-loop Receptorsmentioning
confidence: 99%
“…R271Q та R271L, розташова-ні на зовнішньоклітинному кінці ТМ2-домену, є найбільш частими та найбільш вивченими гіперплексичними мутаціями. Вони успадковуються аутосомно домінантно [65,[77][78][79]. Ці мутації не змінюють кількість гліцинових рецепторів на поверхні клітини, однак сильно впливають на їх чутливість до гліцину та провідність каналів [81,82,90].…”
Section: гіперплексіяunclassified